Juridical Review of the Right to Restitution, Rehabilitation, and Compensation for Victims of the Crime of Trafficking in Persons according to Law No. 21 of 2007 on Court Decisions: Tinjauan Yuridis Hak Restitusi, Rehabilitasi, dan Ganti Rugi Bagi Korban Tindak Pidana Perdagangan Orang Menurut Undang-Undang No 21 Tahun 2007 pada Putusan Pengadilan - Putri, Syntia Puspita Andini Ika Hariyanto; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2022)
The two continents and oceans around Indonesia make Indonesia in the position of international shipping trade routes. However, in the geographical location of the State of Indonesia, it is threatened to become a traffic lane for crime. Trafficking in people or persons is not only a domestic concern, but is a universal problem that is increasing every year. The purpose of this research is to find out or provide knowledge about the fulfillment of restitution rights and rehabilitation rights, and compensation for victims of trafficking in persons which are criminal acts in court decisions. Normative juridical law is the method used by the author in this study. This study provides results that the right to rehabilitation, restitution, and compensation for victims of the Criminal Act of Trafficking in Persons in Decision No. 257/Pid.Sus./2019/PN SDA and Decision No. 889/Pid.Sus/2018/PN SDA according to the Law No. 21 of 2007 was not implemented or not applied by the Panel of Judges.